2020
DOI: 10.1177/0300060520954727
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of transradial coronary intervention for left main bifurcation disease using the new Braidin® slender 7 Fr sheath and a standard 6 Fr sheath

Abstract: Objectives To compare the effectiveness and safety of the Braidin® slender 7 Fr sheath with a standard 6 Fr sheath for treating left main bifurcation disease. Methods From January 2017 to March 2019, 277 patients with left main bifurcation disease who underwent the transradial approach for percutaneous coronary intervention were divided into the slender 7 Fr sheath group (Braidin® slender 7 Fr sheath, n = 154) and standard 6 Fr sheath group (n = 123). Pathological features, surgical effect, and complications w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…A prospective multicentre study recruiting patients undergoing left distal transradial approach for coronary CTO interventions using a 7-Fr Glidesheath Slender found the rate of left distal RAO of 4.3% at the 1-month decteced by Doppler ultrasound [21]. Moreover, previous studies have shown that Braidin slender 7-Fr sheath had a RAO rate of 5.8% at 1 month of followup in 154 patients with left main bifurcation diseases [22]. Isawa et al [23] reported that in the matched patients, the use of 7-Fr Glidesheath slender was significantly less likely to develop ultrasound diagnosed RAO (1.4% vs. 4.1%) at 30 days compared to the use of 7.5-Fr Sheathless system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A prospective multicentre study recruiting patients undergoing left distal transradial approach for coronary CTO interventions using a 7-Fr Glidesheath Slender found the rate of left distal RAO of 4.3% at the 1-month decteced by Doppler ultrasound [21]. Moreover, previous studies have shown that Braidin slender 7-Fr sheath had a RAO rate of 5.8% at 1 month of followup in 154 patients with left main bifurcation diseases [22]. Isawa et al [23] reported that in the matched patients, the use of 7-Fr Glidesheath slender was significantly less likely to develop ultrasound diagnosed RAO (1.4% vs. 4.1%) at 30 days compared to the use of 7.5-Fr Sheathless system.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective multicentre study recruiting patients undergoing left distal transradial approach for coronary CTO interventions using a 7-Fr Glidesheath Slender found the rate of left distal RAO of 4.3% at the 1-month decteced by Doppler ultrasound [ 21 ]. Moreover, previous studies have shown that Braidin slender 7-Fr sheath had a RAO rate of 5.8% at 1 month of follow-up in 154 patients with left main bifurcation diseases [ 22 ]. Isawa et al .…”
Section: Discussionmentioning
confidence: 99%